Effects of dietary Yucca schidigera on hatchability of Japanese quails - AYASAN, TUGAY (The Indian Journal of Animal Sciences, 2013)
The present study was carried out to determine whether dietary Yucca schidigera powder would affect hatchability parameters of laying Japanese quail (Coturnix coturnix Japonica). In this study, 30 female Japanese quails were used. The experimental quails were divided into 2 dietary treatment groups of similar mean weight comprising 30 birds, which was divided into 3 subgroups of birds. A standard layer feed, basal diet of the trial was supplemented with 0 or 120 ppm Yucca schidigera powder. Feed and water were supplied ad lib. and light was provided 16 h (from 8.00 to 24.00) each day. Results showed that Yucca schidigera supplementation to the diet did not affect hatchability of total eggs set,hatchability of fertile eggs set and fertile egg%